Factors Related to the Success of Exclusive Breastfeeding in the Work Area of the Mubune Community Health Center - Dewiyanti Kiyuk; Rifzul Maulina (International Journal of Public Health, 2025)
Background: Exclusive breastfeeding has been proven to improve the quality of human resources and foster a loving relationship between mothers and their babies. However, the coverage of exclusive breastfeeding in the Mubune Community Health Center (UPTD) working area remains below the target. Objective: This study aims to determine factors associated with the success of exclusive breastfeeding, including family support, employment status, education level, income level, and knowledge level in the Kalumata Community Health Center (UPTD) working area of ​​the Mubune Community Health Center. Method: This study used a cross-sectional design. The results showed that of the 54 respondents (mothers with infants aged <6 months), 44 respondents exclusively breastfed and 10 respondents did not. Results: The results of this study indicate a significant relationship between family support and the success of exclusive breastfeeding with a p-value <0.05 (0.031). While education level, knowledge, employment status, and income did not have a significant relationship, with a p-value >0.05. Conclusion: There is a relationship between family support and the success of exclusive breastfeeding. This study contributes to the study of exclusive breastfeeding success. Recommendation: The need to form a breastfeeding support group to support the success of exclusive breastfeeding in the Mubune Community Health Center (UPTD) work area.